Hormonal treatment with transdermal testosterone in patients with male accessory gland inflammation (MAGI): Effects on sperm parameters. (24th November 2016) - La Vignera, S.; Condorelli, R. A.; Mongioi, L. M.; Vitale, S. G.; Russo, G. I.; Laganà, A. S.; Calogero, A. E.
Summary: Recently, it has been reported that treatment with testosterone (T) could have favourable effects on prostate inflammation; however, the data appear inconsistent. The main evidences concern experimental studies, and there is lower information obtainable from clinical studies. This study was conducted on patients with diagnosis of male accessory gland infection (MAGI) and a concomitant hormonal condition of acquired hypergonadotropic hypogonadism and has evaluated the effects on sperm parameters of the administration of a transdermal formulation of T gel for 3 months. The treated patients showed a significantly increased percentage of spermatozoa with normal form and progressive motility ( p < .05 vs baseline), a significant reduction of CD45pos leucocytes in the semen ( p < .05 vs baseline) and finally a significant increase of the seminal concentrations of zinc, fructose and alpha‐glucosidase ( p < .05 vs baseline) identified as key parameters associated to secretory function of the male accessory glands. The results of this study suggest the use of transdermal T in hypogonadal patients with MAGI for favourable effects on sperm parameters.